Systematics and paleogeographical studies of some species of Bryozoa (Cheilostomata) from the Gulf of Mexico - Simone Pouyet; Yolanda Herrera-Anduaga (Revista Mexicana de Ciencias Geológicas)
Two groups of problematic species of bryozoans (Cheilostomata) from the Gulf of Mexico were analized. The first group contains species of the Genus stylopomaLevinsen, 1909… In order to continue, download the full paper in PDF.